Depressive symptoms are more influenced by personality traits and styles than working in nursing—a study during the COVID-19 pandemic - Maringgele, Victoria Elena; Scherr, Martin; Aichhorn, Wolfgang; Kaiser, Andreas Kurt (Frontiers in Psychology, 2023)
Background: According to literature, the Covid-19 pandemic caused stressful working conditions for nurses, which may have a negative impact on their Well-Being and mental health. Aim: To investigate whether nurses and non-helping professionals differ in their Well-Being. Furthermore, we analyzed, for the first time, which personality traits and styles are a risk factor for nurses’ wellbeing during Covid-19 pandemic. Methods: In an online survey the following psychological tests were used on nursing staff (n = 518) and non-helping professionals (n = 335): WHO-Five (WHO-5), the Personality, Style and Disorder Inventory (PSSI) and the Freiburg Personality Inventory-Revised (FPI-R). Results: Nurses and non-helping professionals did not differ significantly in terms of Well-Being. The Well-Being of nurses was correlated with the following personality traits and styles, namely Spontaneous-Borderline Personality Style, Silent-Depressive Personality Style, Strain, Emotionality, Life Satisfaction. According to our results 33 % of participants suffered from clinically significant depressive symptoms. Discussion: According to our results, nurses are not more at risk for depression. However, it was shown that Well-Being during the pandemic is highly dependent on personality. Conclusions: Specific personality traits and styles are a greater predictor of depressive symptoms than profession. The stressful occupational environment during Covid-19 pandemic is not the only cause for depressive symptoms in nurses. Psychotherapeutic interventions are especially important for particular individuals and are necessary to prevent depressive symptoms during Covid-19 pandemic.